The Last Star - Yancey, Richard (New York, NY : G.P. Putnam's Sons, 2016)
"In the epic conclusion to the 5th Wave series, Cassie, Ben, Ringer, and Evan confront the Others' plans for the fate of the human race and the planet"--
Keywords: Extraterrestrial beings -- Juvenile fiction; War stories; Survival -- Juvenile fiction; Science fiction; Extraterrestrial beings -- Fiction; War -- Fiction; Survival -- Fiction; Science fiction; JUVENILE FICTION / Action & Adventure / General